Hypereosinophilic syndrome with cardiac and neurological involvement in the setting of FIP1L1-PDGFRA-gene rearrangement - W. A. Y. C. Piyarathna; L. Piyasundara; N. Dikmadugoda; M. I. Mujahieth; Y. S. Samaraweera; N. Ranasinghe (Asian Journal of Internal Medicine)
We describe a case of a 62-year-old man with two episodes of ischaemic strokes who was diagnosed to have hypereosinophilic syndrome(HES) with cardiac and neurological involvement. Further workup for causes of hypereosinophilia ruled out secondary(reactive) causes while bone marrow aspiration and trephine biopsy raised the suspicion of clonal eosinophilia which was confirmed by the detection of FIPILI-PDGFRA gene rearrangement in peripheral blood for FISH analysis. He was started on low-dose imatinib for which he showed a good haematological response with normalisation of eosinophil counts.